Transforming Leadership In Libraries Through An Innovative And Motivated Workforce - Mohd Noor, Azahar (2015)
Creating an innovative and motivated workforce has never been more challenging for leadership in libraries. Demands for services frequently outstrip the resources-money, time, and people-that are available. Librarians look for more effective ways to make their voices heard as priorities are set organisation-wide. And the constant expectation that they will provide articulate, effective leadership too often creates stresses in both their personal and professional lives. This paper attempts to examine two key questions : Firstly, how well-positioned are Libraries in organisations to meet current and future challenge?